Obesity-Related Asthma: Immune Regulation and Potential Targeted Therapies. (28th June 2018) - Yuan, Yuze; Ran, Nan; Xiong, Lingxin; Wang, Guoqiang; Guan, Xuewa; Wang, Ziyan; Guo, Yingqiao; Pang, Zhiqiang; Fang, Keyong; Lu, Junying; Zhang, Chao; Zheng, Ruipeng; et al.
Abstract : Obesity, one of the most severe public health problems of the 21st century, is a common metabolic syndrome due to excess body fat. The incidence and severity of obesity-related asthma have undergone a dramatic increase. Because obesity-related asthma is poorly controlled using conventional therapies, alternative and complementary therapies are urgently needed. Lipid metabolism may be abnormal in obesity-related asthma, and immune modulation therapies need to be investigated. Herein, we describe the immune regulators of lipid metabolism in obesity as well as the interplay of obesity and asthma. These lay the foundations for targeted therapies in terms of direct and indirect immune regulators of lipid metabolism, which ultimately help provide effective control of obesity-related asthma with a feasible treatment strategy.